Optimal design of a novel M-like channel in bipolar plates of proton exchange membrane fuel cell based on minimum entropy generation. (1st February 2020) - Wan, Zhongmin; Quan, Wenxiang; Yang, Chen; Yan, Hanzhang; Chen, Xi; Huang, Taiming; Wang, Xiaodong; Chan, Siewhwa
Highlights: An optimization strategy based on minimum entropy generation was established. The novel M-like channel was proposed for the first time in the literature. Irreversibility resulted from heat transfer process overwhelms the others. Maximum power density of M-like channel is 21.3% increment than wave-like channel. Abstract: The geometry of the flow channel in bipolar plates (BPs) significantly influences the performance of proton exchange membrane fuel cells (PEMFCs). Considering this, the present study is aimed at optimizing the flow field in a straight channel by pursuing a minimum entropy generation. In accordance with the optimization strategy established herein, the flow field in a straight channel was optimized by solving the governing equations using COMSOL. Furthermore, a novel M-like channel was designed. Compared with conventional wave-like channels, the M-like channel exhibits lower entropy generation under equal pumping power, which implies higher heat and mass transfer performance. An analysis of the four factors contributing to entropy generation revealed that the irreversibility resulting from the heat transfer process is higher than that from its three counterparts. To further improve the heat and mass transfer performance of the M-like channel, the effects of geometric parameters on the entropy generation were investigated. The polarization curves of the wave-like channel and M-like channel in a single fuel cell were obtained based on the fuel cell and electrolysis module. The numerical results indicated that the maximum power density of the M-like channel is higher than that of the wave-like channel by 21.3%. These results provide effective guidance for the geometric design of a flow field in the BPs of a PEMFC.